Assessment of Heavy Metal Levels in Muscle, Liver and Kidney of Assessment of Heavy Metal Levels in Muscle, Liver and Kidney of Sheep and Goats Slaughtered in Municipality Abattoir of Puducher uducherry, INDIA - R., R. Premanand; Pal, U.K.; Gawdaman, G.; Das , C.D.; Mandal, P.K. (Journal of Meat Science, 2014)
A study was conducted to determine the presence and levels of heavy metals viz. chromium, copper, lead and zinc in muscle, liver and kidney of sheep and goats slaughtered in municipality slaughter house of Puducherry. A total of 144 samples, (24 samples of each tissue for each species) were analyzed using Atomic Absorption Spectrophotometer. Mean values of chromium, copper, lead and zinc recorded in muscle, liver, and kidney of sheep were 4.31 ± 0.24, 2.83 ± 0.18, 2.87 ± 0.26; 1.01 ± 0.03, 27.64 ± 3.92, 3.50 ± 0.16; 4.83 ± 0.26, 4.58 ± 0.32, 4.20 ± 0.34; 31.08 ± 3.45, 37.81 ± 1.50 and 25.08 ± 0.53 ppm, respectively. In goat muscle, liver and kidney they accounted for 1.00 ± 0.04, 1.01 ± 0.06, 1.00 ± 0.08; 0.72 ± 0.03, 4.45 ± 0.75, 5.01 ± 0.59; 4.33 ± 0.25, 4.20 ± 0.24, 4.87 ± 0.33; 28.13 ± 1.89, 11.28 ± 0.88 and 18.94 ± 0.26, ppm, respectively. When comparisons were made between goat and sheep tissues, it was found that sheep muscle, liver and kidney contained significantly (P <0.05) higher concentration of chromium, copper and zinc with the exception that copper concentration was significantly (P<0.05) higher in goat kidney. The concentration of lead recorded in all the tissues (4.20-4.87 ppm) in both the species was higher than the maximum permissible limit (2.5ppm) prescribed by MFPO in meat product. Levels of other three metals in the tissues of sheep and goat recorded in the present study were below the prescribed maximum permissible limit except the concentration of copper in the liver of sheep (30ppm)